„Index Librorum in Bibliotheca Ecclesiae Cathedralis Vilnensis” of 1598 - Pietrzkiewicz, Iwona (Bibliotheca Lituana, 2012)
In Lithuania the earliest collections of books were centered in churches and monasteries. One of them was the library in the Cathedral of Vilnius. „Index librorum, in Bibliotheca Eccles[iae] Cathedralis Vilnensis” was written in 1598 as a part of the inventory of the church. Publication of the inventory is supplemented with comments and an attempt to identify all titles of books. The framework of the collection of books was influenced by internal orders and dispositions of the church authorities as well as the wills of bishops and canons. The writings collected in the Cathedral library were fairly typical for such kind of institutions: the texts of the Church Fathers, theological and philosophical authorities of that time as well as juridical documents. It’s a very interesting historical source, whoch analysis helps us to reconstruct the picture of the intellectual output of priesthood in the diocese of Vilnius at the end of the 16th century.
Keywords: none